New Insights into the Geological Evolution of Eastern Indonesia from Recent Research Projects by the SE Asia Research Group - Watkinson, Ian M.; Hall, Robert; Cottam, Mike A.; Sevastjanova, Inga; Suggate, Simon; Gunawan, Indra; Pownall, Jonathan M.; Hennig, Juliane; Ferdian, Farid; Gold, David; Zimmermann, Sebastian; Rudyawan, Alfend; Advocaat, Eldert (Berita Sedimentologi, 2012)
Eastern Indonesia has a prolonged, complex tectonic history. It is where the Eurasian, Indo-Australian, Caroline and Philippine Sea plates converge, and where processes such as subduction, obduction, slab rollback, rifting, supracrustal extension, lower crustal flow and exhumation are very young or still active.For these reasons, the SE Asia Research Group (SEARG) at Royal Holloway, University of London, has made Eastern Indonesia one of its major research themes in recent years. The SEARG has been conducting geological research in SE Asia since 1982. Work has been undertaken in Indonesia, Malaysia, Thailand, the Philippines, Vietnam and the South China Sea. In 2012 the SEARG is directed by Professor Robert Hall, and involves 12 postgraduate students, 2 postdoctoral researchers, a large number of academic staff, research associates and collaborators in the UK and overseas. The group is funded by a consortium of oil companies.Here we summarise recent and ongoing SEARG projects in Eastern Indonesia. Most of the projects are field-based, but they all also employ new data and techniques, such as 40Ar-39Ar, U-Pb dating (SHRIMP and LA-ICP-MS), Hf isotope dating (LA-MC-ICP-MS), UTh/ He dating, multibeam bathymetry, high quality seismic and remote sensing data.